Analisis Literatur Media Pembelajaran Wordwall dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PAI - Rohmah, Nadia Wulidar (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the use of Wordwall-based learning media in improving student learning outcomes in Islamic Religious Education (PAI). The study used a qualitative approach with a literature study method through the search and analysis of various relevant scientific journals from Google Scholar, SINTA, and nationally reputable journals. The study focused on the implementation of Wordwall in PAI learning, its influence on student motivation and engagement, and its impact on improving learning outcomes. The analysis results show that the use of Wordwall can create more interactive, participatory, and student-centered learning. The available educational game features encourage increased learning interest, activeness, and intrinsic motivation of students. Several studies reviewed also show a significant difference between pretest and posttest scores after the implementation of Wordwall, indicating an increase in learning outcomes. In addition to impacting cognitive aspects, this media also supports character strengthening and internalization of Islamic values ​​contextually. Thus, Wordwall can be categorized as an effective and relevant digital learning media in supporting the improvement of the quality of PAI learning in the technological era.